RESEÑA DE PECES Y PESCA DEPORTIVA ARGENTINA, MAR Y PATAGONIA.: IRIGOYEN, A.; G. TROBBIANI; M. CASALINUOVO; M. ALONSO (eds.) (Natura Neotropicalis, 2019)
IRIGOYEN, A.; G. TROBBIANI; M. CASALINUOVO; M. ALONSO et al., 2018. Peces y pesca deportiva argentina,Mar y Patagonia. IRIGOYEN, A.; G. TROBBIANI; M. CASALINUOVO; M. ALONSO (eds.). Remitente Patagonia,Trelew, Chubut, Argentina, 272 pp.